Contraception method following spontaneous abortion in N'djamena Mother and Child Hospital - Gabkikabray Madoué; Foumsou Lhagadang; Abdelsalam Saleh; Saibana Gama (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Introduction: Contraception is the prevention of pregnancy. It can be offered immediately after a spontaneous abortion. Objective: The aim of this study was to show the characteristics of patients accepting contraception after a spontaneous abortion and the main contraception methods chosen. Method: This was a 5-month prospective survey conducted from July to December 2017at N'djamena Mother and Child Hospital in Chad. Results: Of the135 patients recruited 81 (60%) agreed to use a contraceptive method; 33.3% of these 81 women were aged 20-24 years, and 67.9% chose the injection method of contraception. Conclusion: Contraception methods are often used following a spontaneous abortion by patients at N'djamena Mother and Child Hospital in Chad. Injection was the preferred contraception method.